The Impact of Internal Control and Human Resource Quality on the Financial Reporting at the Regional Finance and Assets Agency of the Kupang City Government - Sandra Riska Ade Irma Benuf (CV. Namora dan Riona Bersaudara, 2026)
This study aims to examine the effect of internal control systems and human resource quality on the quality of financial reporting at the Regional Finance and Assets Agency of the Kupang City Government (Badan Keuangan dan Aset Daerah Kota Kupang). This research employs a quantitative approach using primary data collected through questionnaires distributed to employees involved in financial management. The data were analyzed using multiple linear regression. The results show that the internal control system has a positive and significant effect on the quality of financial statements, indicating that effective control mechanisms contribute to more reliable and accountable financial reporting. In contrast, human resource quality does not have a significant effect, suggesting that standardized systems and procedures may reduce the dependency on individual competencies. Simultaneously, both variables significantly influence the quality of financial reporting, with internal control systems having a more dominant role. This study contributes to the public sector accounting literature by providing empirical evidence on the importance of internal control systems in improving financial reporting quality. Practically, the findings suggest that local government institutions should prioritize strengthening internal control frameworks to enhance transparency and accountability in financial management